2018
DOI: 10.1002/macp.201700524
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Microporous Polytetra(2‐Thienyl)ethylene as High Performance Anode Material for Lithium‐ and Sodium‐Ion Batteries

Abstract: A novel, thiophene‐rich conjugated microporous polymer of polytetra(2‐thienyl)ethylene (PTTE) is synthesized via FeCl3‐catalyzed oxidative polymerization and applied as an anode material for lithium‐ion batteries (LIBs) and sodium‐ion batteries (SIBs). Owing to the high surface area, high redox‐active thiophene content, and the plentiful nanoporous structures in PTTE, the assembled LIBs exhibit a high specific capacitance of 973 mA h g−1 at 100 mA g−1 with excellent rate performance, and the SIBs show a capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 64 publications
(98 reference statements)
1
20
0
Order By: Relevance
“…Powder X-ray diffraction profiles revealed an amorphous structure of the CMPs (Figure S5b), which is in accordance with the reported CMPs. 27,30,46 Scanning electron microscope (SEM) images showed that all the CMPs have nanoparticle morphologies with particle sizes of 30−200 nm, except for PhBT, which exhibits a nanofiber morphology with a diameter of about 15 nm (Figure S6). The nitrogen adsorption−desorption isotherms indicated the existence of abundant micropores in these CMPs, showing high nitrogen adsorption at a low relative pressure (P/P 0 < 0.001, Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Powder X-ray diffraction profiles revealed an amorphous structure of the CMPs (Figure S5b), which is in accordance with the reported CMPs. 27,30,46 Scanning electron microscope (SEM) images showed that all the CMPs have nanoparticle morphologies with particle sizes of 30−200 nm, except for PhBT, which exhibits a nanofiber morphology with a diameter of about 15 nm (Figure S6). The nitrogen adsorption−desorption isotherms indicated the existence of abundant micropores in these CMPs, showing high nitrogen adsorption at a low relative pressure (P/P 0 < 0.001, Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Electrodes built from small organic molecules usually suffer from their high solubility in organic electrolytes, leading to a short cycle life . To mitigate this problem, polymerization is a simple and efficient approach. , The extended backbone and larger molecular weight of polymers can lower their solubility in electrolytes and thus achieve better cycling performance. Porous organic polymers (POPs) are a class of solids which can be either an amorphous or a crystalline framework. They provide a platform which can integrate multiple redox-active sites, rigid frameworks, adjustable pore sizes, and high surface areas at the molecular level .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large size of Na + , attempts have been made to design crystalline solids as electrode materials. , This is due to the belief that the pore sizes in crystalline compounds can be controlled to be large enough to host Na ions and that the structural rigidity of the crystalline solids will help maintain the pore sizes, thus leading to better cycling stability. The crystalline subclass of POPs, known as covalent organic frameworks (COFs), has therefore gained much attention in recent years as potential electrode materials for Na–organic batteries due to their uniform pore sizes and high surface areas. , However, the majority of the porous organic compounds reported for SIBs have been investigated as anodes, and use of these materials as cathodes is still rare. , Generally, synthesis of COFs with uniform pores and channels relies heavily on precise control of the dynamic covalent chemistry, which may be quite challenging to achieve and therefore hampers practical applications of COFs, especially in large-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…As a potential alternative, conjugated polymers are intriguing, as they possess high electrical conductivities and form lightweight electrodes . Recently, various organic materials, such as polydopamine‐derived electrodes, thiophene‐rich conjugated microporous polymers, and conjugated ladder‐structured oligomers, have been proposed and revealed their merits in Li‐ and Na‐ion cells . In particular, the tunable bandgap between highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) accelerates the charge transfer kinetics .…”
Section: Introductionmentioning
confidence: 99%